Implementation of Digital Marketing Learning to Develop Capabilities in Making Video Content Marketing - Farida, Eka (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The aim of this research is to prepare digital marketing teaching materials and test the effectiveness of digital marketing learning to develop the ability to create content marketing videos. Methodology: The method used in the research is experimental and ex-post facto which is explanatory. The experimental method is used to test the effectiveness of digital marketing learning in experimental classes in management study programs. An ex-post facto method to test the effectiveness of digital marketing learning through assessing content marketing videos created by student working groups. Findings: The results of most students' video content marketing assessments are classified as very good. The content marketing video produced by the student working group is in accordance with the learning objectives. The application of digital marketing learning can grow students' ability to create content marketing videos. Implications: Applying digital marketing strategies and learning methods through project-based learning methods can improve students' abilities in creating content marketing videos. Practical implications: The ability to create marketing content videos can be applied through project-based digital marketing learning. Originality/value: The resulting product can be used as a reference for digital marketing learning to grow students' abilities in making content marketing videos, so that learning outcomes are obtained that are in line with the objectives of MBKM. Paper type: Research paper